Relationships between training load, peak height velocity, muscle soreness and fatigue status in elite-level young soccer players: a competition season study - Hadi Nobari; Özgür Eken; Okan Kamiş; Rafael Oliveira; Pablo Prieto González; Rodrigo Aquino (BMC, 2023)
Abstract Background This study aimed to compare training load parameters, delayed onset muscle soreness (DOMS), and fatigue status between season periods (1st and 2nd halves) in U14 soccer players and to analyze the relationships between training load parameters based on season periods (1st and 2nd halves) with peak height velocity (PHV), DOMS, and fatigue status in under-14 (U14) young elite soccer players. Additionally, it was intended to analyze if fatigue, DOMS and PHV could explain training load parameters across the season. Methods Twenty U14 players that competed in the national league participated in this study. The players were monitored during the whole season (26 weeks), and evaluations were carried out at the end of the in-season. Anthropometric and body composition parameters and the maturity offset of each player were utilized to compute each player's age at PHV. Players reported their levels of DOMS and fatigue status using Hooper index questionnaires. The internal load was monitored using the rating of perceived exertion (RPE). Acute weekly internal load (AW), chronic weekly internal load (CW), acute: chronic workload ratio (ACWR), training monotony (TM), and training strain (TS) were also obtained. Results The main results showed that TM was higher in the 2nd half, while CW, AW and DOMS were higher in the 1st half of the season. Moreover, the main correlations showed a positive correlation between PHV and TS (2nd half of the season) and between fatigue and TM (1st half of the season). Conclusion In conclusion, variations in well-being status and PHV cannot explain the variations in internal training loads in elite U14 soccer players. In addition, internal training load indices during the first half of the competitive season can promote a fundamental base for progression loads during the second period of the competitive season.